A new mechanism of belt slip dynamic instability and noise in automotive accessory belt drive systems. (15th March 2007) - Sheng, Gang; Liu, Keming; Brown, Les; Otremba, Jerzy; Pang, Jian; Qatu, Mohamad; Dukkipati, Rao
This paper presents a new mechanism of V-ribbed belt (Micro-V™) dynamic instability and slip noise in accessory belt drive system of automotive engines. In this study, a set of experiments was conducted to investigate the properties of the belt noise and system dynamics using an industry standard test rig. A friction-induced system instability concept is proposed and an illustrative model is presented to elaborate the root cause of the system oscillations and the associated slip noise. This proposed new mechanism has correlated well with experimental results. This study is expected to provide accessory drive designers a completely new way to deal with the issues associated with improving the belt slip noise performance of accessory belt drive system.